Анестезиология ва реанимиматология фанида амалий кўникмаларни ўқитиш ва баҳолаш методикаси - Ахмадалиев, Ш.Ш (SCIENCE and SOCIETY, 2023)
The article presents the latest information about the necessary methods and innovative approaches for effective teach- ing of a number of practical skills included in the science of anesthesiology and resuscitation in medical schools today. In particular, imitation and simulation teaching methods were discussed. Methods of assessment of manual skills are covered.
Keywords: anesthesiology-reanimatology; activity-based assessment; highly realistic simulations; learning effectiveness; profes- sional competence